2001
DOI: 10.1088/0264-9381/18/3/307
|View full text |Cite
|
Sign up to set email alerts
|

Hyperbolic formulations and numerical relativity: II. asymptotically constrained systems of Einstein equations

Abstract: revised version) gr-qc/0007034 to appear in Class. Quant. Grav.)We study asymptotically constrained systems for numerical integration of the Einstein equations, which are intended to be robust against perturbative errors for the free evolution of the initial data. First, we examine the previously proposed "λ-system", which introduces artificial flows to constraint surfaces based on the symmetric hyperbolic formulation. We show that this system works as expected for the wave propagation problem in the Maxwell s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
53
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(59 citation statements)
references
References 35 publications
(57 reference statements)
5
53
1
Order By: Relevance
“…We note that these guidelines are confirmed numerically for wave propagation in the Maxwell system and in the Ashtekar version of the Einstein system [12], and also for error propagation in Minkowskii space-time using adjusted ADM systems [16]. Supporting theorems for above (A) was recently discussed [31].…”
Section: Constraint Propagation Analysis In Flat Space-time a Psupporting
confidence: 64%
See 1 more Smart Citation
“…We note that these guidelines are confirmed numerically for wave propagation in the Maxwell system and in the Ashtekar version of the Einstein system [12], and also for error propagation in Minkowskii space-time using adjusted ADM systems [16]. Supporting theorems for above (A) was recently discussed [31].…”
Section: Constraint Propagation Analysis In Flat Space-time a Psupporting
confidence: 64%
“…Through the series of studies [3,6,12,16], we propose a systematic treatment for constructing a robust evolution system against perturbative error. We call it an asymp-totically constrained (or asymptotically stable) system if the error decays itself.…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is to take as the variables the components of an orthonormal triad and the projection of the extrinsic curvature onto the triad (or the Ashtekar variables [15][16][17]). The triad formalism, because the extrinsic curvature tensor projected on the triad is symmetric, has fewer variables than the mixed coordinate component formalism.…”
Section: B Relevance Of Results and Future Directionsmentioning
confidence: 99%
“…Adding these energy constraint terms to the AY formulation is a special case of the more general Kidder, Scheel, and Teukolsky [19] schemes. Shinkai and Yoneda [15][16][17] analyzed the stability and accuracy properties of first order hyperbolic systems using Ashtekar's connection variables in plane-symmetric spacetimes, and found that the addition of multiples of the constraints to the dynamical equations improved accuracy and stability. These results have been extended to ADM systems of equations [18].…”
Section: Introductionmentioning
confidence: 99%
“…Another possibility is the construction of asymptotically constrained systems that seek to control the violation of constraints by having the constraint surface as an attractor. This includes the λ−system [21,78] and a family of adjusted systems [35,87,88,86]. All these have shown several advantages when compared to the standard ADM formulation [76,67].…”
Section: Introductionmentioning
confidence: 99%